Teologia Universalis: the academic contributions of the Faculty of Theology for Kastamonu University to the International Sciences (Eurasian Journal of Religious Studies, 2021)
Before the establishment of the Republic of Turkey, from the medieval age, Madrasas and other Islamic educational institutions were well-known to be in process of their reformation and development activities in the last period of the Ottoman Era. Religious instruction was also held in those madrasas under some departments such as; 1- Department of Islamic (Shariah) Sciences, 2- Department of Law and Legal Sciences, 3- Department of Fünun (Science), 4- Department of Medical Sciences, 5- Department of Literary Sciences. That Dar al- Funun built in the 1908's Emrullah Efendi's Sharia Sciences (Ulum-ur Şer'iye) as Faculty of Theology in Turkey may be the first core fort his model. On March 3 1924, the Article of "Unification of Education" was issued out. With this constittutional article, a faculty of theology affiliated to Istanbul Darul Fünun was opened. The Faculty of Theology was closed in 1933 and soon after subsequently, the Institute of Islamic Studies was established in Istanbul however in 1936 this institute was closed as well. There has been experienced a dramatic process until 1949 when Ankara University has opended its doors to a newly founded Faculty of Theology. The Democrat Party, which came to power after the 1950 elections, opened Imam Hatip Schools (IHO) in the first year of its ruling times, as it promised for election periods, and this was followed by the opening of Islamic Institutes. In the following periods, schools and faculties providing many religious education were established. The Faculty of Theology belonged to Kastamonu University is one of these institutions. Although it is a newly established young faculty, it has achieved great success and made a fame and global name.  In this article we will deal with its contributions to the global religious studies. Keywords: Religion, Religious Education, Faculty of Theology, Higher Religious Education, Democracy
Keywords: Religion; Religious Education; Faculty of Theology; Higher Religious Education; Democracy